Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan pada Dinas Pekerjaan Umum dan Penataan Ruang Jombang - Anandita, Septian Ragil; Nasrulloh, Muhammad; Mahendri, Wisnu (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study was to determine the effect of Leadership Style and Organizational Culture on Employee Performance at the Department of PUPR Jombang. The method used in this study is a quantitative method. The population in this study amounted to 159 employees while the sample amounted to 60 respondents using the Slovin formula. Data were collected using the questionnaire method, which was then analyzed using multiple regression analysis using SPSS version 25. The results showed that partially the Leadership Style variable had a positive but not significant effect on employee performance, while the Organizational Culture variable had a positive and significant effect on employee performance. Simultaneously, the variables of Leadership Style and Organizational Culture have a positive and significant effect on the Performance of the Employees of the Jombang PUPR Service. The results of the analysis of the coefficient of determination obtained 0.467 or 46.7%, which means that the contribution of the variables of Leadership Style and Organizational Culture to employee performance is 53.3%. While the remaining 53.3% is influenced by other variables outside this regression equation or other variables not examined.